Analisis Isi Soal UAMBN Bahasa Arab Madrasah Aliyah Tahun Pelajaran 2016/2017 dan 2017/2018 - Obi Saepul Bahri (Fakultas Keguruan dan Ilmu Pendidikan Universitas Langlangbuana, 2019)
This content analysis aims to analyze the comparison of language learning content found in the UAMBN Arabic language Aliyah Madrasah between the 2016/2017 Academic Year and 2017/2018 Academic Year. The method used in this study is content analysis using a qualitative research approach. This type of research is descriptive research using documentation techniques. From the results of the 2016/2017 problem analysis, researchers found a question of cultural content and a mindset numbering 14 questions, consisting of 8 cultural content and a mindset of 6. The vocabulary content was 4 questions. The structure content is 31 questions. And the content of the terminology is one question, namely the question 43.